Phenolic compounds, antioxidant and antibacterial activity of extract from leaves and bark of Stryphnodendron adstringens (Mart.) Coville - Emílio Ribeiro da Cruz, Jhonatas (Revista Ciência Agronômica, 2021)
There is currently growing interest in the investigation of bioactive compounds from natural sources. In this context, this study investigated the phenolic content, antioxidant capacity, and antimicrobial activity of the hydroalcoholic extract (EHA) of the stem barks and leaves of Stryphnodendron adstringens. Plant parts were extracted with ethanol:water (1:1) and fi ltered in a vacuum to obtain the crude extract. Phenolic content was determined by the Folin–Ciocalteu method. Antioxidant activity was measured using the DPPH test. The antimicrobial activity of extracts was evaluated against Gram-positive cocci: Staphylococcus aureus (ATCC 25923) and Staphylococcus epidermidis (strain isolated from a patient); and Gram-negative bacilli: Escherichia coli (ATCC 25922) and Pseudomonas aeruginosa (ATCC 27853). The zone of inhibition and the minimum inhibitory concentration (MIC) of the plant extracts were evaluated by the agar diffusion disc method and broth microdilution, respectively. Total phenolic content of the EHAs was higher in stem barks (970.4 mg GAE/g) than in leaves (693.8 mg GAE/g). In the DPPH assay, all extracts showed high antioxidant activity, above 75% at the concentration of 100 μg/mL. About antimicrobial activity, all the EHAs showed effects against Gram-positive bacteria S. aureus and S. epidermidis, whose MIC ranged from 7.81 μg/mL to 62.5 μg/mL. This fi nding is important since these pathogens are generally resistant to a variety of widely known antibiotics. Therefore, these results are promising and indicate the use of S. adstringens (Mart.) Coville as a natural antioxidant in foods, medicines and also point to its use in antimicrobial therapy.